Influence of energy efficient infrastructure, financial inclusion, and digitalization on ecological sustainability of ASEAN countries - Chen, Kenjie; Zhang, Shaohui (Frontiers in Environmental Science, 2022)
ASEAN countries are emerging economies facing substantial, sustainable energy production and consumption challenges. Power sources' availability, sustainability, and efficiency are imperative to ensure ecological sustainability. Therefore, these countries must explore the factors that promote sustainable energy supply. The current study investigates the interlinkages between energy infrastructure, financial inclusion, and digitalization on the ecological sustainability of ASEAN region from 1980 to 2018. The study applied the continuously updated fully modified (CUP-FM) and continuously updated bias-corrected (CUP-BC) estimators to address cross-sectional dependency and slope heterogeneity issues. The study's findings show that energy infrastructure, financial inclusion, and digitalization help to reduce ecological footprints in the long run. Moreover, digitalization complements the impact of energy-efficient infrastructure on ecological footprints. These findings recommend that ASEAN countries should improve energy infrastructure by integrating digitalization into energy supply production, management, and distribution.